Lifestyle Characteristics of Poor and Rich People in Poland - Sączewska-Piotrowska, Anna; Piotrowski, Damian (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The health of individuals and communities depends on various factors. Medical condition is mostly related to unhealthy characteristics such as smoking, heavy alcohol consumption, obesity and lack of physical activity. These characteristics may occur singly or they can accumulate which can contribute to serious diseases at very young age. The lifestyle vary depending on socio-economic characteristics of people, e.g. age, sex, education, place of residence, income, kind of job. The aim of this paper was to compare lifestyle characteristics of poor and rich people. The attention was paid on certain unhealthy characteristics: alcohol consumption, smoking, overweight and obesity, and physical activity. There were compared shares of smoking, drinking too much alcohol, overweight and obese, and physically inactive among poor, middle class and rich people. The shares of leading a healthy lifestyle (no unhealthy characteristics) were also compared. The logistic regression models were estimated to determine the impact of economic situation to lifestyle behaviour (controlling for other variables: sex, age, education and place of residence). Using the odds-ratios there was evaluated the relationship between cigarette smoking and other unhealthy characteristics
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 387-401
Keywords: lifestyle; poverty; richness; health